Exploring Contextual Factors in English Pronunciation Accuracy: Insights from Indonesian EFL University-Level Learners - Ristati, Ristati; Bahing, Bahing; Haryani, Tutik; Retsi, Olga Dona; Amalia, Novika (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This research investigates how various contextual factors influence the accuracy of English pronunciation among Indonesian EFL learners. Motivation, exposure to the second language (L2), formal education, and interference from the first language (L1) are explored to address a gap in understanding their combined impact. Employing an explanatory sequential approach, the research gathers quantitative data through questionnaires and pronunciation tests administered to 30 EFL learners, selected using cluster sampling from a total of 80 students across three classes. Qualitative insights were then obtained from five randomly chosen participants in follow-up interviews. The quantitative data were analyzed using descriptive and correlational statistics, while the qualitative data were examined through deductive thematic analysis. The findings reveal that L1 interference has the strongest impact on pronunciation accuracy, particularly in fricatives and diphthongs, where learners substitute unfamiliar sounds with native ones. L2 exposure significantly improves pronunciation, especially through authentic media and interactions. Motivation, while influential, indirectly aids pronunciation by fostering self-directed learning. However, formal education has minimal impact, as pronunciation receives little focus in traditional classrooms. These results highlight the need for targeted phonetic training, immersive exposure, and explicit pronunciation instruction. The study calls for pedagogical reforms to enhance communicative competence and confidence.